Alairhynchus, a new name for the genus Gigantorhynchus Sapelnikov & Malygina 1977 (Brachiopoda: Camarotoechioidea) preoccupied by Gigantorhynchus Hamann 1892 (Vermes: Acanthocephala) - Doweld, Alexander B. (Zootaxa, 2013)
The genus Gigantorhynchus (type species = G. dubius Sapelnikov & Malygina, 1977, by original designation) was established by Sapelnikov & Malygina (1977: 62) for a distinctive fossil brachiopod from Eastern Alai (Southern Tien Shan, Kyrgyzstan) which subsequently served as type of a subfamily (Gigantorhynchinae Savage 1996). However, the name Gigantorhynchus was preoccupied by a living worm genus published by Hamann (1892: 196) (Vermes: Acanthocephala: Gigantorhynchida: Gigantorhynchidae Hamann 1892). The worm Gigantorhynchus is well recognized in modern zoology, serving as type of a distinct order and family (Gigantorhynchida and Gigantorhynchidae Hamann 1892, respectively).